The Landdroskop area in the Hottentots Holland Mountains as a refugium for melanistic lizard species : an analysis for conservation - Costandius, Eloise (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MSc (Botany and Zoology))--University of Stellenbosch, 2005.